A national survey of caregiver's own experiences and perceptions of U.S. health care system when addressing their health and caring for an older adult - Jill C. Slaboda; Sandahl H. Nelson; Zia Agha; Gregory J. Norman (BMC, 2021)
Abstract Background Caregiving is a demanding role that can negatively impact a person's health and well-being. As such, adequate access to health care is important for maintaining the family caregiver's own personal health. The aims of this study were to identify if family caregivers of older adults had more difficulty accessing health care services than non-caregivers and to identify if family caregivers felt access to additional services would be beneficial for maintaining their own personal health care. Methods National survey of 3026 US adults aged 30 to 89 years old. Participants were grouped based on self-reported caregiving experience. Survey asked about access to care, importance of health care services and whether caregivers had support needed. Descriptive statistics were used to compare caregiver and non-caregiver's responses. Multivariate logistic regression model assessed correlates of caregivers not having the support they needed. Results Caregivers were older, female, lower educational attainment, lower income, had more multiple chronic health conditions and health condition or disability that impacts their daily life. Caregivers reported difficulty accessing mental health services, dental services, medications, and supportive services at home. Caregivers felt it was important to have care coordinator, long-term relationship with primary care provider and access to house calls, telemedicine, and medications delivered to the home. Age, ethnicity, chronic conditions and confidence in finances were factors influencing whether caregiver had support needed to provide assistance to older care recipient. Conclusion Caregivers provide needed support and care to older adults while also needing support for themselves. Health care services delivered in the home were highly desirable to caregivers and could help them maintain their health and well-being.